Exploring High Voltage Potential of 3D Printed Capacitors: A Filament-Based Comparison Through Dielectric Performance Analysis - Uydur, Cihat Cagdas; Akin, Firat (MDPI, 2024)
Recent advancements in 3D printing technology have enabled the rapid production of complex structures, yet the dielectric performance of 3D printing materials and their potential for manufacturing electrical components remain insufficiently studied. In this study, a capacitor rated at 10 kV with a capacitance of 1 nF was designed and developed for high-voltage applications. During the production of the capacitor, the insulating and conductive parts were fabricated using a 3D printer. While PLA, ABS, ASA, and PETG were employed as insulating materials, aluminum was chosen as the conductive part. Theoretical calculations and the finite element method were used to validate the measured capacitance of the equipment. The performance of the prototype capacitor was analyzed through partial discharge inception voltages (PDIV), dissipation factor (tan delta), and breakdown voltage measurements. Dissipation factor measurements were performed at 2 and 4 kV voltages in the 50-400 Hz frequency range. The performance of employed materials was comparatively analyzed through experimental and simulation results. Finally, the impact of different insulating materials on the dielectric performance of the prototype capacitors was evaluated.
Keywords: high voltage; capacitor; electric field distribution; dissipation factor; partial discharge; 3D printer; ABS; PLA; ASA; PETG; insulation co-ordination; Chemistry; Engineering; Materials Science; Physics